Uji Kekerasan Pada Sprocket Gear Dengan Perlakuan Panas 600°C Dan Di Quenching Dengan Pelumas SAE 40 - Ahmadin ahmadin (MAJALAH TEKNIK SIMES, 2020)
Abstract A gear is a part of a rotating machine and is useful for transmitting power. Motorcycle gear sprocket is one of the components driving the wheels. This component is one of the most important components. The type of material used in this component is included in the type of low carbon steel.Heat treatment, heat treatment and cooling quickly to get the properties of changes in carbon steel, metal or guide. One method of treatment is the quenching process. This process was carried out at 600C for 30 minutes then cooled with SAE 40 lubricant cooling media. The test results showed that the hardness value on the gear sprocket decreased after undergoing a quenching process, with a non-treatment hardness value of 84.04 HRB and a hardness value with heat treatment of 78.26 HRB.